Fragmented care and whole-person illness: Decision-making for people with chronic end-stage kidney disease. (March 2015) - Allen, Dawn; Badro, Valerie; Denyer-Willis, Laurie; Ellen Macdonald, Mary; Paré, Anthony; Hutchinson, Tom; Barré, Paul; Beauchemin, Roch; Bocti, Helen; Broadbent, Alison; Cohen, S Robin
Purpose: The study reported herein sought to better understand how patients with multi-morbid, chronic illness—who receive care in institutions designed for treatment of acute illness—experience and engage in health-related decisions. Methods: In an urban Canadian teaching hospital, we studied the interactions of six hemodialysis patients and 11 of the health professionals involved in their care. For 1 year (September 2009 to September 2010), we conducted ethnographic observation and interviews of six cases each comprising one hemodialysis patient and various health professionals including medical specialists, nurses, a social worker, and a dietician. Results: We found that the ubiquity and complexity of health-related decision-making in the lives of these patients suggests the need for a more holistic interpretation of health-related decision-making. Discussion: We propose an interpretation of decision-making as an ongoing process of integrating illness and life; as frequently open-ended, cumulative, and relational; and as fundamentally shaped by the fragmented delivery of care for patients with multiple morbidities. Conclusion: Our understanding of decision-making suggests that people living with complex chronic illness need to receive care from institutions that recognize and address their multi-morbidity as a whole illness that is constantly being integrated into the life of a whole person.